Formation of second-stage intermediates in anion-exchange intercalation reactions of the layered double hydroxide [LiAl2(OH)(6)]Cl center dot H2O as observed by time-resolved, in situ X-ray diffraction - Fogg, A; Dunn, J; O'Hare, D (1998)
Time-resolved in situ energy-dispersive X-ray diffraction studies on the intercalation of dicarboxylate anions (Na2C4H4O4, Na2C6H8O4, Na2-trans-C4H2O4, Na2-cis-C4H2O4, Na2-L-C4H4O5, Na2-1,2-C8H4O4, Na2-1,4-C8H4O4) into [LiAl2(OH)6]Cl·H2O have revealed the rapid formation of a second-stage intermediate phase that subsequently transforms into a phase-pure fully ion-exchanged product. These intermediates can be isolated as pure crystalline phases by reaction of the host lattice with stoichoimetric amounts of the dicarboxylate anions.